Dietary intervention in obese dams protects male offspring from WAT induction of TRPV4, adiposity, and hyperinsulinemia. Issue 6 (23rd April 2016) - Janoschek, Ruth; Bae‐Gartz, Inga; Vohlen, Christina; Alcázar, Miguel A. Alejandre; Dinger, Katharina; Appel, Sarah; Dötsch, Jörg; Hucklenbruch‐Rother, Eva
Abstract : Objective: One major risk factor for childhood overweight is maternal obesity. The underlying molecular mechanisms are ill‐defined, and effective prevention strategies are missing. Methods: Diet‐induced obese mouse dams were changed to standard chow during pregnancy and lactation as an intervention against predisposition for obesity and metabolic sequelea in the offspring. Expression of adipokines and TRPV4, a regulator of adipose oxidative metabolism, inflammation, and energy homeostasis, in offspring's white adipose tissue (WAT) was assessed. Results: Pathological effects on offspring's body weight, fat content, and serum insulin were fully reversed in intervention offspring on postnatal day 21. In WAT, a sixfold increase of Trpv4 mRNA expression in offspring consuming high‐fat‐containing diet was found, which was completely blunted in the intervention group. Simultaneously, WAT adipokine, interleukin‐6, and peroxisome proliferator‐activated receptor‐γ mRNA and UCP1 protein expression were largely returned to control levels in intervention offspring. Conclusions: Improvement of maternal nutrition offers a powerful strategy to improve offspring's metabolic health. Targeting TRPV4‐linked aspects of WAT metabolic function during early development might be a promising approach to prevent long‐term adverse metabolic effects of maternal high‐fat nutrition.